Exploration of screening practices for obstructive sleep apnea in stroke medical community: A pilot study. Issue 2 (June 2016) - Navalkele, Digvijaya D.; Barlinn, Kristian; Minagar, Alireza; Chernyshev, Oleg Y.
Abstract: Background: Frequency of sleep-disordered breathing (SDB) among stroke and transient ischemic attack (TIA) patients ranges from 30–80% and is associated with poor neurological outcomes. Per current stroke prevention guidelines from American Heart Association/American Stroke Association (AHA/ASA), SDB is included in the list of modifiable risk factors for stroke and TIA prevention. Goal of our study is to determine screening practices for SDB in stroke medical community. Methods: A web-based survey was sent to physicians taking care of stroke patients across North America and Europe. Results: Among 112 total responses, 91 (81%) were stroke physicians, nine (8%) were general neurologists, nine (8%) were from other specialties and three (3%) were sleep medicine physicians. Majority of physicians (72%, n = 81) do not use SDB screening questionnaires in their stroke patients. Epworth sleepiness scale is the most used among SDB questionnaires (24%, n = 25/105), followed by Berlin sleep questionnaire (10%) and STOP-BANG questionnaire (7%). Only 13% of physicians use screening questionnaires in both in-patients and outpatients, whereas 21% use only in outpatients and 5% use only in acute stroke setting. Only 50% (n = 56/111) of physicians would refer their stroke patients to a sleep medicine specialist when patients screen positive for SDB on questionnaires. Conclusion: Despite being an independent risk factor for stroke and TIA, majority of physicians in the pilot targeted cohort of medical professionals, who are involved in the management of stroke and TIA, do not screen these patients for SDB. Further work involving systematic, more detailed standardized surveys are needed to be developed to objectively evaluate and improve screening practices for SDB in national and international stroke medical communities.